The validity of the shadowbox™ magnetic and inertial motion tracking system for measuring soccer-specific movements (7th World Congress on Science and Football (WCSF), 2011, 2011)
There are some motion-tracking technologies, such as GPS, that can effectively measure global movements made by soccer players on the field [1]. However, it has been difficult for sport scientists to remotely measure the soccer-specific actions of players such as kicking, tacking, passing the ball and gait biomechanics during a game. The purpose of this study, therefore, was to evaluate the validity of the 3D displacement data derived by a portable and miniature magnetic and inertial motion tracking system, the Shadowbox™ (Shadowbox, Park City, USA), against a criterion camera-based 3D motion capture system, the Vicon MX™ (Vicon Motion systems Ltd, Oxford, UK), during a series of soccer-specific actions. Methods A male subject was asked to perform a kick (drive) of a ball, a one-touch pass and a slide tackle with a Shadowbox™ attached firmly to his right ankle. The Shadowbox™ hardware contained a triaxial accelerometer, gyroscope and magnetometer which sampled at 600 Hertz. The raw data was converted into 3D displacement data using a quaternion filter method [2]. A reflective marker was placed on the Shadowbox™. This enabled the previously calibrated Vicon MX™ strobe cameras to precisely track the displacement of the Shadowbox™ during each trial. Results & Discussion Displacement data from the Shadowbox™ and Vicon MX™ motion tracking systems had a high Pearson correlation coefficient and variance explained (R2). The Shadowbox™ system, therefore, tracked the ankle during soccer specific actions with the same accuracy and precision as the criterion method. Conclusion The Shadowbox™ motion tracking system was proven to have high validity against the criterion method, the Vicon MX™ motion tracking system, during a series of soccer specific movements including kicking a ball, one-touch pass of a ball and a slide tackle.